Injury Patterns and Causes of Death Among Occupants of Three-wheelers Succumbed to Their Injuries From Road Traffic Accidents in Sri Lanka - Nishantha Vadysinghe, Amal; Mudiyanselage Kasun Dhananjaya Katugaha, Bandaranayake Herath; Piyarathna, Chathura; Mahinda Colombage, Senerath (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: In Sri Lanka and South Asian countries, three-wheeler vehicles are a popular mode of transportation. However due to poor vehicle safety features and road conditions, this vehicle is more vulnerable to accidents. In this regard, we hypothesize that the occupants of three-wheelers sustain a different pattern of injuries compared to occupants of other vehicles, which cause a fatal outcome. Methods: This was a retrospective study from 2005 to 2014. The study samples were occupants of three-wheelers succumbed from road traffic accidents reported to 3 medico-legal units in Sri Lanka. Results: In our study, majority of the victims were young males. The commonest site of fatal injury was head (78.8%), which was more common in passengers. The commonest skull fracture was on base (70.5%). Majority had brain contusion (36.4%) and subarachnoid haemorrhage (31%) was the commonest type of intracranial haemorrhage. Chest injuries directly contributed to death in 57 cases while rib fractures were seen in all such cases. Spinal injuries were seen in 41(31%) cases where cervical spine injuries were the commonest which was seen in 30(73.2 %) cases. In the present study, 65.2% of deaths have taken place within the first hour following the incident. Out of all the fatal cases, 84.8% of the victims were trapped inside the vehicle and others (15.2%) were thrown away. Toppling of the three-wheeler was seen in 27.3% of cases. Conclusion: The poor safety structure of the three-wheeler plays a major role in the type of injuries sustained by the deceased and the safety of the occupants should be improved.